Investment facilitation and the GATS: Do overlaps matter? - Rudolf Adlung; Pierre Sauvé; Sherry Stephenson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
WTO talks on investment facilitation, launched at the 11th Ministerial Conference in 2017, have garnered significant traction, with negotiations currently involving over 100 Members. Looking ahead, a key challenge will be securing an open plurilateral agreement that bridges definitional and conceptual gaps between proposed investment facilitation and existing GATS disciplines.
Keywords: 330